PERLINDUNGAN HUKUM ATAS LAMBANG PALANG MERAH DI INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Kasih Rahayu (PREMISE LAW JURNAL, 2013)
The legal basis for the protection of the Red Cross emblem in Indonesia has been included in the International humanitarian law and the laws and regulations in Indonesia. Protection of the Red Cross emblem in Indonesia in Article 6 paragraph (3) letter (b) of Law Number 15 of 2001, Ditjend. Intellectual Property Rights will reject an application that uses the brand that imitate or resemble the symbol of the Red Cross Indonesia, although not listed in the Ditjend. Intellectual Property Rights, because the Red Cross emblem is a symbol of the international agency's position where the institution is recognized by the Government of Indonesia. Indonesia Red Cross emblem should be given legal protection because it is an internationally recognized symbol of possession by the Indonesian government as a consequence of judicial participation in the Geneva Conventions Indonesia Year 1949. Kata Kunci : Legal Protection, Red Cross, Brand